Hsp90 Inhibitors Inhibit the Entry of Herpes Simplex Virus 1 Into Neuron Cells by Regulating Cofilin-Mediated F-Actin Reorganization - Song, Xiaowei; Wang, Yiliang; Li, Feng; Cao, Wenyan; Zeng, Qiongzhen; Qin, Shurong; Wang, Zhaoyang; Jia, Jiaoyan; Xiao, Ji; Hu, Xiao; Liu, Kaisheng; Wang, Yifei; et al. (Frontiers in Microbiology, 2022)
Herpes simplex virus 1 (HSV-1) is a common neurotropic virus, the herpes simplex encephalitis (HSE) caused by which is considered to be the most common sporadic but fatal encephalitis. Traditional antiviral drugs against HSV-1 are limited to nucleoside analogs targeting viral factors, which lead to a frequent emergence of drug-resistant viral strains. Inhibition of heat shock protein 90 (Hsp90) have potent anti-HSV-1 activities via numerous mechanisms, but the effects of Hsp90 inhibitors on HSV-1 infection in neuronal cells, especially in the phase of attachment and penetration, are still unknown. In this study, we aimed to investigate the effects of Hsp90 inhibitors on HSV-1 infection of neuronal cells. Interestingly, we found that Hsp90 inhibitors promoted viral adsorption but inhibited subsequent penetration in neuronal cell lines and primary neuron, which jointly confers the antiviral activity of Hsp90 inhibitor. Mechanically, Hsp90 inhibitors mainly impaired the interaction between Hsp90 and Cofilin, resulting in a reduced membrane localization of Cofilin, which in turn, led to F-actin polymerization to promote viral attachment. However, excessive polymerization of F-actin inhibited subsequent viral penetration. Consequently, unidirectional F-actin polymerization limits the entry of HSV-1 virions into neuron cells. Our research extended the molecular mechanism of Hsp90 in HSV-1 infection in neuron cells and provided a theoretical basis for the development of antiviral drugs targeting Hsp90.